PENYULUHAN PERLINDUNGAN SISWA DAN UPAYA PREVENTIF PERUNDUNGAN (BULLYING) DI LINGKUNGAN SEKOLAH DASAR - Rommy Hardyansah; Fayola Issalillah; Rafadi Khan Khayru; Rahayu Mardikaningsih; Mila Hariani; Didit Darmawan (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2026)
Bullying behaviour within educational institutions causes serious harm to pupils’ mental and psychological well-being, social relationships and academic achievement, whilst also undermining the creation of a safe and orderly classroom environment. Cases of bullying of this nature are still frequently encountered at various levels of the education system, including at primary madrasah level, thus necessitating concrete preventive measures through an awareness-raising campaign involving all members of the school community. The implementation of this community service programme is aimed at raising the level of awareness and concern amongst pupils, teachers and parents regarding the harmful risks of bullying, whilst strengthening their ability to tackle and mitigate such behaviour. The activity took place at MI Miftahul Ulum, Pasinan Village, utilising a Participatory Action Research (PAR) framework that prioritised the full involvement of all participants through awareness-raising sessions and joint discussions. The findings from the programme demonstrated a significant increase in participants’ understanding of the dangers of bullying and the preventative measures that can be implemented. Through this awareness-raising initiative, it is hoped that MI Miftahul Ulum will be able to foster a much more conducive educational environment for the safety of all pupils.